The Influence of Financial Literacy and Financial Technology on the Quality of Financial Statements - Purwanti, Rizki; Agustin, Khairunnisa; Sari, Kartika; Fitriani, Novi; Irawan (CV Raskha Media Group, 2025)
This study examines the impact of financial literacy (the ability to understand and manage financial concepts) and financial technology (the use of digital tools to record, manage, and report finances) on the quality of financial reports (relevance, consistency, accuracy, and timeliness). Using a quantitative approach through a questionnaire survey of accounting students, the analysis includes validity, reliability, classical assumptions, and multiple linear regression tests. Results: Financial literacy has a significant positive effect on report quality; financial technology is not partially significant; together, the two contribute 34.8%, with the remainder influenced by other factors. This study is expected to enrich accounting theory and provide practical guidance for improving reporting standards.